1996
DOI: 10.1111/j.1559-1816.1996.tb00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Job‐Content Versus Job‐Context Information: A Field Study of the Roles of Need for Closure and Prior Preferences

Abstract: A field study was conducted in a job‐interview setting among female secretarial job applicants with previously expressed preferences for receiving information either about job content or about job context. The results showed that (a) under high as opposed to low need for closure, job applicants requested more job information, whether for job content or job context; (b) across experimental conditions, subjects preferred job‐context information; (c) high need for closure selectively reduced the job‐context infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Hence, people with high need for closure typically show an aversion for high-uncertainty situations and have been found to engage in various activities in order to reduce this uncertainty across different contexts. For instance, Ellis (1996) examined the influence of need for closure on preferences for receiving information in a job interview setting among female secretarial job applicants. The results showed that under experimentally induced high need for closure, job applicants requested more job information, as opposed to under situations of low need for closure.…”
Section: Integrating Uncertainty Reduction and Self-verificationmentioning
confidence: 99%
“…Hence, people with high need for closure typically show an aversion for high-uncertainty situations and have been found to engage in various activities in order to reduce this uncertainty across different contexts. For instance, Ellis (1996) examined the influence of need for closure on preferences for receiving information in a job interview setting among female secretarial job applicants. The results showed that under experimentally induced high need for closure, job applicants requested more job information, as opposed to under situations of low need for closure.…”
Section: Integrating Uncertainty Reduction and Self-verificationmentioning
confidence: 99%
“…In those circumstances, individuals may suspend judgment and be quick to engender alternatives to any emergent view. (p. 264) The closedness for new information and evidence is one of the most important implications of need for closure theory, and has been illustrated by a lowered sensitivity to alternative hypotheses (Kruglanski & Mayseless, 1988) and preference for simplified judgment (Van Hiel & Mervielde, 2003a;Webster & Kruglanski, 1994), but also by a higher resistance to persuasion (Kruglanski, Webster, & Klem, 1993), and a less extensive search for information (Ellis, 1996;Klein & Webster, 2000;Kruglanski, Peri, & Zakai, 1991;Van Hiel & Mervielde, 2002). Moreover, need for closure has also been shown to influence a variety of classic social cognitive phenomena such as the impressional primacy effect (Freund, Kruglanski, & Shpitzajzen, 1985;Heaton & Kruglanski, 1991;Kruglanski & Freund, 1983;Webster & Kruglanski, 1994;Webster, Richter, & Kruglanski, 1996), recency effects (Richter & Kruglanski, 1998), construct accessibility effects (Ford & Kruglanski, 1995), the mere exposure effect (Kruglanski, Freund, & Bar-Tal, 1996), the overattribution bias (Webster, 1993), conformity pressure (De Dreu, 2003), and the use of cognitive heuristics such as numerical anchoring (Kruglanski & Freund, 1983).…”
mentioning
confidence: 97%